Acoustic radiation force impulse (ARFI) elastography of the bowel wall as a possible marker of inflammatory activity in patients with Crohn's disease. Issue 7 (July 2018) - Goertz, R.S.; Lueke, C.; Wildner, D.; Vitali, F.; Neurath, M.F.; Strobel, D.
Abstract : Aim: To evaluate acoustic radiation force impulse (ARFI) shear-wave velocities of the bowel wall in patients with Crohn's disease (CD). Material and methods: ARFI shear-wave elastography was analysed within the wall of the stomach, terminal ileum, and sigmoid, and correlated with ultrasound signs of activity in CD patients both retrospectively and in a prospective cohort. results: A total of 77 retrospective and 21 prospective CD patients were included. ARFI elastography in the stomach, the normal ileum, and sigmoid was lower than in ileitis or sigmoiditis. Retrospectively, the ARFI values correlated with the bowel wall thickness and Limberg vascularisation score. Prospectively, there was no correlation between ARFI and bowel wall thickness, Limberg score, clinical activity, or C-reactive protein. A cut-off analysis of 105 ileal ARFI measurements showed a cut-off value of 1.92 m/s for the diagnosis of ileal inflammation with 75.3% sensitivity and 87.5% specificity. conclusion: In patients with CD, ARFI shear-wave velocities show a trend to higher values in inflamed bowel wall thickening on B-mode ultrasound; however, the differences appear small and may not be clinically significant. The factors influencing ARFI measurements of the bowel wall require further investigation. Highlights: ARFI elastography of the bowel wall in Crohn's disease is feasible. Retrospectively, ARFI elastography correlated with bowel wall thickness and Limberg-vascularisation score. Prospectively, no ARFI correlation achieved statistical significance either with clinical activity or with bowel wall thickness. A trend to higher ARFI shear wave velocities was observed in cases of sonographic signs of inflammation. There is a need to standardize the examination procedure and to detect further influencing factors.